Who Needs Bereavement Support? A Population Based Survey of Bereavement Risk and Support Need - Aoun, Samar M.; Breen, Lauren J.; Howting, Denise A.; Rumbold, Bruce; McNamara, Beverley; Hegney, Desley (PLOS ONE, 2015)
This study identifies and describes the profiles of bereavement risk and support needs of a community sample in Australia and tests the fit of the data with the three-tiered public health model for bereavement support. Family members who were bereaved 6–24 months prior to the survey and who were clients of four funeral providers participated (May-July 2013). A postal survey was used to collect information about bereaved people’s experience of caring and perceived satisfaction with any bereavement support provided. The questionnaire included a validated risk assessment screening measure for Prolonged Grief Disorder (PG-13). A total of 678 bereaved people responded. The model predicted that 60% of the sample would be low risk, 30% moderate risk, and 10% high risk. Actual figures were very close at 58.4%, 35.2% and 6.4% respectively. The analysis of the demographic characteristics, experience and impact of caring and bereavement, and satisfaction with support received from a variety of sources revealed differential experiences and needs that align with the expectation of low, moderate, and high bereavement support need, as articulated in the public health model. This is the first empirical test of the public health model of bereavement support. As there is a lack of clear evidence to guide development and allocation of bereavement support programs, the findings have the potential to inform the ability of services, community organizations and informal networks to prioritize care according to each level of bereavement need. This is essential to achieve cost-effective and equitable resource allocation.